Measurement of non-linear optical coefficients of chalcogenide glasses near the fundamental absorption band edge - Romanova, Elena; Kuzyutkina, Yulia; Shiryaev, Vladimir; Abdel-Moneim, Nabil; Furniss, David; Benson, Trevor; Seddon, Angela; Guizard, Stephane (Elsevier, 2018)
A time-resolved pump-probe method is used for the evaluation of non-linear optical coefficients of chalcogenide glasses from the As-S-Se and Ge-Se systems near their fundamental absorption band edges. The results are analyzed via comparison with the spectral dependencies of the non-linear optical coefficients of crystalline semiconductors; the role of electron transitions through the gap states of chalcogenide glasses is discussed.